The Use of Poster-Making for Social Justice: Engaging Non-English Department Students in Visual Learning - Rizqiani, Diyah Ayu; Roziah, Roziah; Idayani, Andi; Triastuti, Missi (Universitas Pendidikan Mandalika, 2025)
This research investigates the use of poster making to teach social justice issues to undergraduate students of Law and Criminology at a private Islamic university situated in Pekanbaru, Indonesia. Adopting a qualitative case study approach, the study focused on 54 students and their creation of posters on human trafficking, corruption, and cyber crimes. Data were gathered through a peer-assessment rubric with five major indicators: poster appeal, graphic support, slogan, delivery, and time management. Findings revealed that students’s scores for time management (M = 4.06) were the highest and for slogan writing (M = 3.69) were the lowest, suggesting that students were more proficient in collaboration than in persuasive expression. Poster qualitative analysis highlighted the students’ perception of injustice and their call to action through the use of symbolic and powerful imagery of chains, blindfolds, cuts of striking women in red, and simplistic, yet evocative, text. These elements illustrated a heightened sense of awareness, ethical reasoning, and empathy. The results highlight the feasibility of incorporating poster making as a form of instructional practice in social justice pedagogy in law and criminology alongside other non-humanities programs within Islamic universities in Indonesia.